(untitled) (Research, Society and Development, 2021)
The internships in teacher training enable experiences in the field of education that need to be socialized. With this in mind, this article sought to analyze the contributions present in the observation stage, of a graduate student in Biological Sciences from a Brazilian public institution, located in the northwest region of the state of Rio Grande do Sul, paying attention to an epistemic and analytical debate in the field of education, with a view to promoting a rethinking of teacher training in a remote teaching context. The adopted methodology consisted of a qualitative research, of the descriptive type, whose data collection was done through a logbook and, for the analysis of the data, we opted for the Discursive Textual Analysis. Remote activities, due to the pandemic caused by the New Coronavirus, bring with them challenging situations, both for teachers, as well as for interns and students. In this sense, it is plausible to say that internships provide opportunities for new experiences, allowing one to (re) think about the teacher’s performance for the mediation of knowledge in contemporary times.